Camel milk regulates T‐cell proliferation to alleviate dextran sodium sulphate‐induced colitis in mice. (20th November 2019) - Cui, Changwan; Lu, Yiping; Yue, Yuanyi; Wu, Si; Wang, Shuang; Yu, Miao; Sun, Zhengrong
Summary: The incidence of inflammatory bowel disease (IBD) is increasing in China. Current clinical methods of treatment for IBD are accompanied by side effects, and thus, the search for effective therapeutic drugs with minimal adverse effects is necessary. In the present study, the effects of camel milk (CM) on dextran sodium sulphate (DSS)‐induced acute and chronic colitis in a mouse model were investigated. The results showed CM effectively alleviated the injury induced by DSS to the colon mucosa and imbalance of immune cells in mice. However, treatment with CM significantly increased the body weight of mice and decreased the disease activity index (DAI), histopathological score, proliferation of Th17 cells and concentration of inflammatory cytokine IL‐17. The results from the present study indicate CM possesses intestinal protective effects. Abstract : The graphical abstract demonstrated the main results of our study. This research investigated the effect of camel milk (CM) on the process of colitis in mice. CM could regulate the internal homeostasis by reducing pro‐inflammatory cell proliferation and differentiation, and up‐enhancing anti‐inflammatory cells in the colons of mice.